2017
DOI: 10.1177/0890334417711385
|View full text |Cite
|
Sign up to set email alerts
|

Use of Videoconferencing for Lactation Consultation: An Online Cross-Sectional Survey of Mothers’ Acceptance in the United States

Abstract: This sample of mothers indicated general acceptance of videoconferencing for lactation consultation, with younger mothers and those perceiving it to be more useful demonstrating greater acceptance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
2
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 19 publications
(39 reference statements)
0
2
2
1
Order By: Relevance
“…Those more likely to be willing to use telelactation were married, in a higher income bracket, white, and had experience using videochat platforms, suggesting lower-income, nonwhite participants may have lower uptake of telelactation programs. These results differ from the only other quantitative study of the acceptability of telelactation, which found no significant differences in willingness to use the technology based on sociodemographic factors [14]. Our results suggest willingness to engage in telelactation may be contingent on a multitude of factors.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Those more likely to be willing to use telelactation were married, in a higher income bracket, white, and had experience using videochat platforms, suggesting lower-income, nonwhite participants may have lower uptake of telelactation programs. These results differ from the only other quantitative study of the acceptability of telelactation, which found no significant differences in willingness to use the technology based on sociodemographic factors [14]. Our results suggest willingness to engage in telelactation may be contingent on a multitude of factors.…”
Section: Discussioncontrasting
confidence: 99%
“…Results in other studies indicate that telelactation is a viable alternative to in-person lactation support for some populations [13][14][15]17,20]; however, our findings suggest it may not be acceptable to all. The complexity of acceptability of telelactation is supported by other findings from this study.…”
Section: Discussioncontrasting
confidence: 56%
See 1 more Smart Citation
“…(35) With the advent of smartphones and more universal access to the internet, the conditional use of telelactation consultation is widely accepted. (36) The previously reported demographic characteristics such as maternal level of education, maternal age, or maternal socioeconomic status did not appear to influence a mother's acceptance of telelactation. This study highlights both the extent to which technology has become embedded within our day-to-day activities and the increased facility of the general population with electronic devices and applications.…”
Section: Telelactationmentioning
confidence: 75%
“…Antes da pandemia de COVID-19, a telelactação era praticada, tendo sido registrada boa aceitação de videoconferência para atendimentos à lactação entre puérperas (72) . Consultadoras de amamentação, em que 73% do atendimento foi realizado de forma online na atual pandemia, relataram ser notória a satisfação das lactantes pelo serviço prestado, principalmente por estarem com a rede de apoio reduzida, possibilitando a promoção do aleitamento materno e saúde mental das lactantes (54) .…”
Section: Discussionunclassified